2017
DOI: 10.1002/jssc.201601269
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of 13 carbohydrates using high‐performance anion‐exchange chromatography coupled with pulsed amperometric detection and mass spectrometry

Abstract: A simple, accurate, and highly sensitive method was developed for the determination of 13 carbohydrates in polysaccharide of Spirulina platensis based on high-performance anion-exchange chromatography coupled with pulsed amperometric detection and mass spectrometry. Samples were extracted with deionized water using ultrasonic-assisted extraction, and the ultrasound-assisted extraction conditions were optimized by Box-Behnken design. Then the extracted polysaccharide was hydrolyzed by adding 1 mol/L trifluoroac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The average absorbance of three parallel validation experiments at 530 nm was 1.295, which was well matched with the predicted value with a relative error of 7.48%, indicating that the model was suitable for synthetic condition optimization of CAO-AuNPs [21,27]. …”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…The average absorbance of three parallel validation experiments at 530 nm was 1.295, which was well matched with the predicted value with a relative error of 7.48%, indicating that the model was suitable for synthetic condition optimization of CAO-AuNPs [21,27]. …”
Section: Resultsmentioning
confidence: 56%
“…Additionally, the “Adeq Precision” of 9.685 in our experiment indicated that the model with an adequate signal was suitable for the optimal design of this experiment. This RSM model was confirmed to fit the experimental optimization of synthesis of AuNPs well [21,22,27]. The 3D profiles and contour plots of multiple non-linear regression models (Figure S3) were depicted as a graphical interpretation of the experimental levels of each independent variable.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…The extra acid was completely removed by adding methanol with rotary evaporation [ 25 ]. The monosaccharides were analysed by high-performance anion-exchange chromatography coupled with pulsed amperometric detection (HPAEC–PAD) method [ 26 ]. HPAEC–PAD analysis was performed using an ICS-5000+ ion chromatography system that consisted of a quaternary pump, temperature-controlled column manager, and ED5000 PAD electrochemical cell which consisted of an Au working electrode and pH-Ag/AgCl reference electrode.…”
Section: Methodsmentioning
confidence: 99%
“…This interface resulted in greater ionization efficiency of mono/di-saccharides for the analysis of neutral sugars in pectin samples that were separated with HPAEC 66 . In another study, 13 monosaccharides from polysaccharide from Arthrospira ( Spirulina) platensis (both neutral ones and acidic, carboxy, sugars that are already negatively charged at neutral pH) were simultaneously separated through a gradient elution of sodium hydroxide and sodium acetate with HPAEC coupled to both PAD and MS detectors 67 . Although separation of the neutral monosaccharides can be increased when a lower pH is used for the alkaline eluent since both neutral and acidic, carboxylated, sugars were analyzed, it was found that a higher concentration of NaOH was necessary for the desired separation 67 .…”
Section: Analytical Toolbox Of Chromatographic Modesmentioning
confidence: 99%